Complementary and alternative asthma treatments and their association with asthma control: a population-based study. Issue 9 (4th September 2013) - Chen, Wenjia; FitzGerald, J Mark; Rousseau, Roxanne; Lynd, Larry D; Tan, Wan C; Sadatsafavi, Mohsen
Abstract : Objectives: Many patients with asthma spend time and resources consuming complementary and alternative medicines (CAMs). This study explores whether CAM utilisation is associated with asthma control and the intake of asthma controller medications. Design: Population-based, prospective cross-sectional study. Setting: General population residing in two census areas in the province of British Columbia, Canada. Recruitment was based on random-digit dialling of both landlines and cell phones. Participants: 486 patients with self-reported physician diagnosis of asthma (mean age 52 years; 67.3% woman). Primary and secondary outcome measures: We assessed CAM use over the previous 12 months, level of asthma control as defined by the Global Initiative for Asthma and the self-reported intake of controller medications. Multivariate logistic regression was performed to study the relationship between any usage of CAMs (outcome), asthma control and controller medication usage, adjusted for potential confounders. Results: A total of 179 (36.8%) of the sample reported CAM usage in the past 12 months. Breathing exercises (17.7%), herbal medicines (10.1%) and vitamins (9.7%) were the most popular CAMs reported. After adjustment, female sex (OR 1.66; 95% CI 1.09 to 2.52) and uncontrolled asthma (vs controlled asthma, OR 2.25, 95% CI 1.30 to 3.89) were associated with a higher likelihood of using any CAMs in the past 12 months. Controller medication use was not associated with CAM usage in general and in the subgroups defined by asthma control. Conclusions: Clinicians and policy makers need to be aware of the high prevalence of CAM use in patients with asthma and its association with lack of asthma control.